Analisis Resepsi Komunitas Binaraga Deltoidz mengenai Sensualitas dalam Iklan Televisi Pond’s Men - Ivan Maulana; Altobeli Lobodally (UNIVERSITAS KALBIS, 2022)
Sensuality in television commercial (TVC) is still considered as an attractive things to get the attention from the audience. Many brands assume that ads on the television can be accepted by the audience. The audience that consuming media categorized as passive and accepting all the content on media. However, in reality the audience is active and they don’t take it for granted. The aim of this research is to find out reception of Deltoidz bodybuilder community about sensuality on Pond’s Men Lightning Oil Clear TVC. The research uses qualitative approach, with Reception Analysis method, and Encoding-Decoding Theory. This research uses In-depth interview to collecting data from Deltoidz bodybuilder community. The results of this research is from all five informants, three informants categorized in Hegemonic-Domination position, one informant categorized in Opposition position, and one informant categorized in Negotiation position. Each informant interpreted it based on their knowledge and experience of sensuality.